Effect of Pestle needle combined with Six Healing Sounds Qi Gong on inflammatory factors in patients with lumbar disc herniation: Pestle Needle and Qi Gong for Lumbar Disc Inflammation - Chen, Junzhu; Huang, Xiaohui; Liu, Chaofan; Feng, Yue; Zhang, Shurong; Wang, Qi; Wang, Fang (Journal of Medical Biochemistry, 2025)
Background: To evaluate the impact of combining Pestle needle therapy with Six Healing Sounds Qi Gong exercises on serum inflammatory markers in patients with lumbar disc herniation. Methods: Ninety-six patients with lumbar disc herniation (LDH) were randomly assigned to three groups with 32 patients in each group. Group A received standard LDH treatment and care, while Group B received Pestle needle therapy in addition to the standard treatment of Group A. Group C incorporated the Six Healing Sounds Qi Gong in addition to the treatments in Group B. All three groups underwent treatment for four weeks. Comparisons of serum levels of IL-1β, IL-6, TNF-α, and CRP, as well as evaluations using the VAS, the ODI, and JOA score, were conducted among the groups before and after treatment. Results: Following treatment, the levels of serum inflammatory markers, as well as VAS score and ODI score, in both Group B and Group C, were significantly reduced compared to their pre-treatment levels (P < 0.05). Additionally, the JOA score in these groups was significantly increased compared to pre-treatment values (P < 0.05). These improvements were notably greater than those observed in Group A (P < 0.05). Except for IL-1β, the improvements in the other indices in Group C were significantly better than those in Group B (P < 0.05). Conclusions: The combination of pestle needle and Six Healing Sounds Qi Gong exercise therapy can effectively reduce serum levels of serum inflammatory markers in patients with LDH. This approach helps alleviate lumbar pain and improve lumbar function.